Audio-Visual Aids in EFL classroom : integrating technology in language teaching according to students' learning styles (2013)
Through this paper, our aim is to present and discuss the findings of a research study conducted by Mathew and Alidmat (2013) on “the Usefulness of Audio-Visual Aids in EFL Classroom: Implication for Effective Instruction”. However, we also want to go beyond, and expand the concept about audio-visual aids citing some researchers that can explain different issues related to the topic in order to build an idea about the importance of integrating these technological aids in the process of learning a foreign language, but taking into account that not all learners achieve language objectives in the same way. Before starting to discuss the article, it is important to state some ideas that can be meaningful to understand the topic and the arguments we are going to present.